2005
DOI: 10.1111/j.1744-7909.2005.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Roots of Anemone altaica Fisch. ex C. A. Mey.

Abstract: The roots of Anemone altaica Fisch. ex C. A. Mey. have been used in the treatment of epilepsia, neurasthenia, and arthritis in Chinese folk medicine for a long time. In order to find new and bioactive compounds, the chemical constituents of the roots of A. altaica were investigated and nine compounds were isolated from the EtOH extract of this plant. On the basis of spectroscopic methods, the structures of these compounds were elucidated as 4-(9H-β-carbolin-1-yl)-4-oxo-butyric acid (1), carboxymethyl isoferula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…In thin layer chromatography (TLC) analysis, compound 4 showed Rf value 0.5 in solvent system n-Hexane: Methanol (80:20) in the form of single band on silica gel plate. Uridine has identical spectral data and chemical properties to those reported in earlier for uridine [23][24][25][26].…”
Section: Resultssupporting
confidence: 67%
“…In thin layer chromatography (TLC) analysis, compound 4 showed Rf value 0.5 in solvent system n-Hexane: Methanol (80:20) in the form of single band on silica gel plate. Uridine has identical spectral data and chemical properties to those reported in earlier for uridine [23][24][25][26].…”
Section: Resultssupporting
confidence: 67%
“…A. altaica grows widespread throughout Northern Asia and Europe. Modern pharmacological studies have suggested the potential anti-inflammatory and analgesic properties of the A. altaica, which has long been used in the treatment of epilepsy, neurasthenia and arthritis in traditional Chinese medicine (Zou et al, 2005). Previous studies were only limited to the study of the chemical constituents and essential oils of A. altaica.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were only limited to the study of the chemical constituents and essential oils of A. altaica. Isolation, purification and structural identification of some small-molecule active ingredients were the focus of previous studies (Feng, 1998;Zou and Yang, 2008;Man et al, 2012). However, in various areas of cancer research, A. altaica extract has not been reported to exhibit antitumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi is some fungi that lives in all kinds of tissue and organ internal or intercellular space in healthy plants with certain stage or the whole stage of its life history [5]. Endophytic fungi can produce some chemical substances, which its structure is similar with host plant, and many compounds have novel structural framework [6]. In 1993, an endophytic fungi isolated from Taxomyces andreanae produced the bioactive compounds, taxol and taxane, just like the host plant.…”
mentioning
confidence: 99%